Literacy on the Utilization of Digital Financial Applications for Cash Books at Siti Noryati Kabuau Schedule Store - Muhammad Rejal; Sri Hastuti; Dwi Orbaningsih; SBP Handajani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of Community Service (PKM) is to bring educational institutions closer to the community, so that universities can help the community in the fields of education, counseling, development of human resources and community knowledge and economic welfare. Community service to MSMEs Siti Noryati's grocery store inabuau is to record financial transactions using the bukukas application in a simple manner. the method used is Participatory Rural Appraisal (PRA), namely approaches and techniques for involving the community in thought processes that take place during planning activities to provide assistance to shopkeepers. The results of this activity are that MSMEs players can operate transactions in Bukukas, and can find out the cost of goods sold, make financial records, accounts payable, profit and loss and make financial reports.